Immersing Islamic Value in English Language Teaching: A Challenge for English Teachers - Wahyu Indah Mala Rohmana (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2020)
Recently the issue of integrating religion view into all life aspects has emerged rapidly. It has something to do with building especially children’s character since they were a child. Moreover, cases of students who lack of norms and attitudes are growing immensely. Hence, the integration of religion in this case Islamic value into all subjects at school is urgently needed. In English Language Teaching (ELT), immersing Islamic value has been constrains by English Teachers because of the limitation of knowledge. Therefore, this paper presents and discusses the values and ethics in Islam its forms and sources. It shades more lights on the infusion of Islamic values and ethics in ELT, the role of teachers, challenges faced in embedding Islamic values into English materials. This paper uses qualitative descriptive research. Library research was used by taking into account some journals and sources related with instilling Islamic values in English teaching. The data then is explained by using descriptive analysis. Finally, this study concludes with some recommendations for tracking the challenges such as inserting exercise with Islamic values in the English topics, using Islamic names for person, event or places, connecting the relevant verse of Holy Book or using it as the material to be translated and using English books containing Islamic messages.